Barriers to glucagon-like peptide-1 agonists used for obesity management among the general population in Tabuk City, Saudi Arabia, and their relation to smoking cessation and antidepressants - Alhowiti, Amirah; Mirghani, Hyder; Abdulrahman Qrmli, Abdulaziz; Albalawi, Amal Abdullah; Abdulrahman Aljohani, Raneem (Frontiers in Pharmacology, 2025)
BackgroundObesity is a chronic inflammatory disease with high morbidity that is decidedly prevalent worldwide and in Saudi Arabia. Glucagon-like peptide 1 receptor agonists (GLP-1 agonists) are broadly used for the management of diabetes and obesity. We aimed to assess barriers to GLP-1 agonist use among the general population in Saudi Arabia and their association with smoking and antidepressants use.MethodsThis cross-sectional study was conducted in Tabuk, Saudi Arabia from January to October 2024 using a structured questionnaire based on age, sex, lifestyle, GLP-1 agonists, antidepressant use, source of information regarding GLP-1 agonists, type of injection, smoking status, and whether smoking frequency/amount decreased following GLP-1 agonists use.Resultsout of the 481 participants, 28.4%, and 30.7% were on regular exercise and a healthy diet respectively, and 21.8% were using GLP-1 agonists of them, 54.5%, and 42.7% interrupted their GLP-1 agonists due to shortage/cost and side effects. Semaglutide was the most common GLP-1 agonist used (13.7%). No significant associations were found between GLP-1 agonist use, age, smoking, and depression (odds ratio, 0.978, 1.073, and 0.770, respectively). A significant association was found with gender, BMI, diet, and exercise.ConclusionGLP-1 agonist uptake was relatively low, the majority of patients used GLP-1 agonists for weight reduction and not for comorbidities. More than half interrupted their intake due to cost/unavailability. Semaglutide was the most commonly prescribed medication. No significant associations were found between GLP-1 agonists use, age, smoking, and antidepressant medication use, a significant association was found with females, BMI, diet, and exercise.